2004
DOI: 10.1002/elps.200305677
|View full text |Cite
|
Sign up to set email alerts
|

Defining the plant disulfide proteome

Abstract: There is considerable interest in redox regulation and new targets for thioredoxin and glutaredoxin are now being identified. It would be of great benefit to the field to have a list of all possible candidates for redox regulation--that is all disulfide proteins in plant. We developed a simple and very powerful method for identifying proteins with disulfide bonds in vivo. In this method, free thiols in proteins are fully blocked by alkylation, following which disulfide cysteines are converted to sulfhydryl gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 52 publications
(54 reference statements)
1
56
0
Order By: Relevance
“…4]. Affinity purification and identification of cellular disulfide-containing proteins by mass spectrometry (SI Table 1) reveal nine proteins, seven of which are cell-surface membrane proteins known to contain disulfides, which is consistent with studies in plants (11) and E. coli (12) reporting that, under normal growth conditions, most proteins containing disulfides are secreted or membrane-bound. Upon treatment with the mitochondrial uncoupler carbonylcyanide m-chlorophenylhydrazone (CCCP), the overall signal decreased (Fig.…”
Section: Resultssupporting
confidence: 77%
“…4]. Affinity purification and identification of cellular disulfide-containing proteins by mass spectrometry (SI Table 1) reveal nine proteins, seven of which are cell-surface membrane proteins known to contain disulfides, which is consistent with studies in plants (11) and E. coli (12) reporting that, under normal growth conditions, most proteins containing disulfides are secreted or membrane-bound. Upon treatment with the mitochondrial uncoupler carbonylcyanide m-chlorophenylhydrazone (CCCP), the overall signal decreased (Fig.…”
Section: Resultssupporting
confidence: 77%
“…Yano et al used monobromobimane to label free thiols in proteins reduced by Trx that were resolved via two-dimensional gel electrophoresis and identified five Trx targets in peanut seeds (26). The Trx affinity technique was subsequently developed to identify Trx targets in diverse cell types, including spinach (27)(28)(29)(30)(31), Arabidopsis (32)(33)(34)(35), Escherichia coli (36,37), wheat seeds (38,39), Synechocystis (40 -42), and HeLa cells (16,43). The most successful of these studies identified up to 80 putative Trx targets (37).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, we used the isotope-coded affinity tag approach to identify over 70 targets of Trx1 transnitrosylation and 50 targets of Trx1-mediated denitrosylation (43). Although a Trx mutant has been used to identify Trx targets in non-mammalian cells (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)44), its application in the identification of mammalian targets has been rare, presumably because of the presence of highly abundant cytosolic targets in the total cell lysates, such as Prx1, that compete for a limited number of binding sites on the Trx1 C35S mutant. This is the first report demonstrating that an nTrx1 C35S mutant can be used to identify novel Trx1 targets in the nucleus of mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…Such a mode of activation, in which an enzyme of the lumen is rendered active when oxidized in the light, contrasts with the mechanism functional in the stroma. The relation of electron transfer proteins of the lumen (36) [HCF164 (37), thylakoid luminal protein (38), oxygen-evolving enhancer protein (39), and CcdA (40)] to the scheme depicted in Fig. 5 …”
Section: Fkbp13 Is a Target For Reduction By Thioredoxinmentioning
confidence: 99%